Effect of Cold on Renal Metabolism in Adult Humans: Perspective in Relation to Obesity. - Zaidi, Syeda (My University, 2024)
Background/Purpose: The development of obesity predisposes humans to severe metabolic implications like type 2 diabetes, chronic kidney disease, etc. Brown adipose tissue (BAT), the body’s thermogenic fat, has recently emerged as an organ of interest involved in energy expenditure and glucose homeostasis. The human kidneys are metabolically active and require high energy to perform their role in maintaining glucose homeostasis. Cold stress activates BAT for non-shivering thermogenesis facilitated by mitochondrial uncoupling protein 1 (UCP-1). However, the effect of cold on systemic metabolism, in addition to BAT activation, is unknown; in particular, it is unclear how cold influences renal metabolism. The methodological advancements in positron emission tomography (PET) imaging have made the study of renal glucose and free fatty acid metabolism non-invasively feasible. Aims: This clinical study aimed to evaluate the effect of acute cold stress on renal metabolism and understand whether brown fat metabolism is related to renal metabolism in the cold. It assessed renal metabolism in humans with normal weight and with obesity by analysing their renal glucose uptake (GU) and free fatty acid uptake (FAU) in the renal cortex and medulla using PET imaging. Study Design/Methods: PET-CT/MR imaging used two different radiotracers, i.e. [18F]-Fluorodeoxyglucose (18F-FDG) and 14(R, S)-[18F] Fluoro-6-thia-heptadecanoic acid (18F-FTHA) which are the radio-analogues of glucose and free fatty acid, respectively. These radiotracers were used to investigate renal glucose and free fatty acid uptakes in the renal cortical and medullary regions at room temperature (RT) and upon acute cold stress. The study cohort comprised 73 healthy human adults, including humans with the lean phenotype (n=37) and humans with the obese phenotype (n=36) of both sexes (21 M / 52 W). A part of the study participants was scanned with 18F-FDG (n= 38; 8 M / 30 W), and a part was scanned with 18F-FTHA radiotracer using PET imaging (n= 35; 13 M / 22 W). Results: In humans with normal weight, exposure to cold neither changed renal GU nor FAU. In humans with obesity, exposure to cold significantly reduced renal GU; however, renal FAU remained unaffected. At RT, humans with normal weight and humans with obesity had similar renal GU; however, during cold stress, humans with obesity had significantly lower GU than humans with normal weight. Both at RT and cold, renal FAU did not differ between humans of a lean phenotype and humans of an obese phenotype. Interestingly, cold-stimulated BAT FAU significantly correlated with renal cortical and medullary FAU. Additionally, renal GU correlated inversely with glycated haemoglobin (HbA1c) during cold stress. Conclusion: In obesity, cold stress affects renal glucose metabolism, while renal fatty acid metabolism is unaffected. The blunted renal glucose metabolism during stress conditions may be a factor in the predisposition to impaired glucose homeostasis in obesity. Further, the fatty acid metabolism of BAT and kidneys is linked during cold stress, suggesting that the presence of active BAT may also represent a superior renal capacity to utilise circulatory free fatty acids.
Keywords: Brown adipose tissue (BAT), PET-CT/MRI, Glucose uptake (GU), Free fatty acid (FFA), Free fatty acid uptake (FAU), Positron emission tomography (PET), 14(R, S)-[18F] Fluoro-6-thia-heptadecanoic acid (18F-FTHA), [18F]-Fluorodeoxyglucose (18F-FDG).